Uji Efektivitas Berbagai Surfaktan pada Insektisida Tenchu dalam Menanggulangi Hama Thrips sp. pada Tanaman Induk Acacia crassicarpa di Rumah Tanaman Induk Kerinci Central Nursery 1 East - Gerry; Yuslinawari (Fakultas Kehutanan Institut Pertanian STIPER Yogyakarta, 2023)
The Nursery Department is the department responsible for ensuring the success of Acacia crassicarpa plants at an early stage by caring for and maintaining the quality and quantity of the seeds before planting them in the planting area. One of the disturbances that threatens the quality and quantity of seed production is the presence of Thrips sp. pest attacks. One of the Thrips sp. pest control techniques. with the application of insecticides with appropriate surfactants. Therefore, it is necessary to test various surfactants on Tenchu ​​20 SG insecticides which are appropriate in tackling Thrips sp. pest attacks. This study aims to determine the most appropriate surfactant in the Tenchu ​​20 SG insecticide in tackling Thrips sp. which attacks the mother plant Acacia crassicarpa. This research was conducted using a completely randomized design (CRD) with Least Significant Difference (LSD) follow-up test. The number of treatments in this study consisted of 5 treatments where each complete treatment with 3 repetitions used 72 sample plants so that the total sample plants used were 360 ​​plants. The parameters observed were the incidence and severity of Thrips sp.. The results showed that there was a decrease in the incidence and severity of Thrips sp. the largest is the type of Ronstick surfactant. The incidence rate and severity of Thrips sp. before application, namely 100% while after application, the incidence rate of Thrips sp. that is equal to 66.67% and the severity of Thrips sp. that is equal to 38.43%.